From the public to the private: the digitization of scholarship - White, Andrew (Palgrave, 2014)
Depending on your perspective, digital media threatens to either destroy or revolutionize millennia-old scholarly practices. The way in which we seek information online as a means of helping us to construct knowledge differs significantly from tried and trusted academic methods. This would not be significant if we did not use the Internet so much for this specific purpose, but, as will be outlined in more detail throughout this chapter, even those of us who carry out academic research are increasingly reliant on the Internet. For this reason, we need to understand both how we search for information online and the extent to which our online practices help or hinder us in our quest for knowledge.